Use of spermatocrit to estimate sperm concentration of semen from piabanha (Brycon insignis) - Shimoda, Eduardo; Andrade, Dalcio Ricardo de; Vidal Junior, Manuel Vazquez; Yasui, George Shigueki; Godinho, Hugo Pereira; Silva, José Frederico Straggiotti; Sousa, Guilherme (Brazilian Journal of Veterinary Research and Animal Science, 2007)
The aim of this work was to determine the viability of spermatocrit use in Piabanha's sperm concentration estimation. Gametogenesis of piabanha Brycon insignis (n=29) was induced with crude pituitary extract of carp and semen was further collected. The spermatocrit was determined using cappilar tube micro-centrifuge. The sperm concentration was verified by counting in "Neubauer chamber", after dilution. The verified sperm concentration (mean±standard deviation) was 24,38±3,84x10(9) spermatozoa/mL, and the spermatocrit was 16,14±5,20%. The regression model: v = 14,01.10(9) + 0,6428.10(9).X was significant (P<0,01) and presented adjusted R² = 0,75. Thus, the estimation of sperm concentration using the spermatocrit is possible.